Synthesis, Antiinflammatory and Antibacterial Activities of4-Substituted Phenyl Benzimidazoles - Leonard, J.T.; Jeyaseeli, L.; Rajesh, O.S.; Murugesh, K.; Sivakumar, R.; Gunasekaran, V. (Asian Journal of Chemistry, 2010)
A new series of substituted benzimidazoles as 1-(substituted methyl)-2-(substituted phenyl) benzimidazoles were synthesized and characterized by IR, 1H NMR and elemental analysis. The compounds were evaluated for antiinflammatory and antibacterial activities. All the compounds exhibited significant to moderate antiinflammatory and antibacterial activities.